Perbedaan Motivasi Belajar Antara Siswa Laki-laki Boarding Dengan Non Boarding Di SMA Al-Islam 1 Surakarta - Salam, Abdus, Setiyo Purwanto, S.Psi. M.Si (2016)
In the world of education, motivation to learn is indispensable due to their motivation to learn, it will grow the strength, energy, and encouragement of individuals to drive, steer, and awaken a passion for learning, increased skills, improve behavior, attitude and personality cemented. This study aims to determine the difference between students' learning motivation boarding with non-boarding students at SMA Al Islam 1 Surakarta. The hypothesis put forward by the authors are learning motivation There is a difference between students boarding with non-boarding students at the high school students of Al Islam 1 Surakarta. The population in this study were male students SMA Al Islam 1 Surakarta. The sampling technique used is non-random sampling, the number of subjects as many as 60 people consisting of 30 students boarding and non-boarding students 30. The method of using a quantitative approach to measuring instrument scale, the scale of motivation to learn. The analysis technique used is Independent Samples Test. The results of the data analysis of the correlation coefficient t of -1.662 with a significance of 0.102 (p ≥ 0.05), so the hypothesis is not accepted, there is no significant difference on the scale of motivation to learn. Motivation to learn classified in the high category with a mean empiric in students boarding at 162.8667 while the non-boarding students at 156.2333 and hypothetical average of 125. Keywords: motivation to learn, boarding and non-boarding.